Development of a Low-cost Pressure Sensor - Rónai, László; Lénárt, József; Szabó, Tamás (International Journal of Engineering and Management Sciences, 2020)
In this paper development of a pressure sensor has been discussed. The main benefit of this sensor is relatively cheap compared to commercially available ones. The unit contains a beam type load cell and a pneumatic cylinder. The load cell has 4 strain gauges in Wheatstone bridge configuration in order to convert the change of resistance into measurable voltage. The system is well applicable in numerous circumstances, where digital pressure signal is necessary for control or data acquisition.